Scalable, Non-denaturing Purification of Phosphoproteins Using Ga3+-IMAC : N2A and M1M2 Titin Components as Study case - Adams, Michael; Fleming, Jennifer R.; Riehle, Eva; Zhou, Tiankun; Zacharchenko, Thomas; Markovic, Marija; Mayans, Olga (My University, 2019)
The purification of phosphorylated proteins in a folded state and in large enough quantity for biochemical or biophysical analysis remains a challenging task. Here, we develop a new implementation of the method of gallium immobilized metal chromatography (Ga3+-IMAC) as to permit the selective enrichment of phosphoproteins in the milligram scale and under native conditions using automated FPLC instrumentation. We apply this method to the purification of the UN2A and M1M2 components of the muscle protein titin upon being monophosphorylated in vitro by cAMP-dependent protein kinase (PKA). We found that UN2A is phosphorylated by PKA at its C-terminus in residue S9578 and M1M2 is phosphorylated in its interdomain linker sequence at position T32607. We demonstrate that the Ga3+-IMAC method is efficient, economical and suitable for implementation in automated purification pipelines for recombinant proteins. The procedure can be applied both to the selective enrichment and to the removal of phosphoproteins from biochemical samples.
Keywords: 570